In the Shadow of the Tower: The View of the Undergraduate Experience - Gomme, Ian M.; Hall, Mary P.; Murphy, Terry J. (Canadian Journal of Higher Education, 1993)
This paper reports the initial findings of a survey (N=388) conducted in Winter 1991 focusing on the quality of the academic experience for Arts and Science students at a medium size post-secondary institution in eastern Canada. Our purposes are: 1) to set out the context in which undergraduates conduct their academic work, 2) to document what their experience entails, and 3) to present some of their perceptions of the higher education process. While most students have vocational goals in mind, they are also keenly interested in acquiring a solid general education. Undergraduates attend most of their classes, are heavily committed to completing their programs, and work quite diligently in pursuit of their goals in the face of what many of them consider to be heavy workloads. They are not, however, completely satisfied with the services that they receive in return for their tuition fees and for Canadians' tax dollars. While satisfaction levels vary with the type of services provided, it is clear that there does exist substantial room in which institutions can make improvements. Specifically, our data suggest that the primary goals of universities seeking to better the undergraduate experience should be to encourage more effective teaching and its evaluation, to reduce class sizes, to increase formal and informal interaction among faculty members and students, to improve the quality of academic advising, and to support the creation of more equitable financial assistance programs for students.